IVF/ICSI outcomes after culture of human embryos at low oxygen tension: a meta-analysis - Gomes Sobrinho David B; Oliveira Joao Batista A; Petersen Claudia G; Mauri Ana L; Silva Liliane FI; Massaro Fabiana C; Baruffi Ricardo LR; Cavagna Mario; Franco José G (BMC, 2011)
Abstract Background Improved pregnancy, implantation, and birth rates have been reported after the use of reduced O2 concentration during embryo culture, mainly due to a reduction of the cumulative detrimental effects of reactive oxygen species. However, some studies have failed to report any positive effects. The objective of this meta-analysis was to evaluate the effect of a low-O2 environment on IVF/intracytoplasmic sperm injection (ICSI) outcomes. Methods All available published and ongoing randomised trials that compared the effects of low (~5%; OC~5) and atmospheric (~20%; OC~20) oxygen concentrations on IVF/ICSI outcomes were included. Search strategies included online surveys of databases from 1980 to 2011. The outcomes measured were fertilisation rate, implantation rate and ongoing pregnancy rates. The fixed effects model was used to calculate the odds ratio. Results Seven studies were included in this analysis. The pooled fertilisation rate did not differ significantly (P = 0.54) between the group of oocytes cultured at low O2 tension and the group at atmospheric O2 tension. Concerning all cycles, the implantation (P = 0.06) and ongoing pregnancy (P = 0.051) rates were not significantly different between the group receiving transferred sets containing only OC~5 embryos and the group receiving transferred sets with only OC~20 embryos. In a meta-analysis performed for only those trials in which embryos were transferred on day 2/3, implantation (P = 0.63) and ongoing pregnancy (P = 0.19) rates were not significantly different between the groups. In contrast, when a meta-analysis was performed using only trials in which embryos were transferred on days 5 and 6 (at the blastocyst stage), the group with transferred sets of only OC~5 embryos showed a statistically significantly higher implantation rate (P = 0.006) than the group receiving transferred sets with only OC~20 embryos, although the ongoing pregnancy (P = 0.19) rates were not significantly different between the groups. Conclusions Despite some promising results, it seems too early to conclude that low O2 culture has an effect on IVF outcome. Additional randomised controlled trials are necessary before evidence-based recommendations can be provided. It should be emphasised that the present meta-analysis does not provide any evidence that low oxygen concentration is unnecessary.